2005
DOI: 10.1016/j.femsec.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and seasonal variation of the cyanobacterial assemblage in a rice paddy field in Fujian, China

Abstract: Cyanobacteria are one of the main components of the microbiota in rice paddy fields and significantly contribute to its fertilization. The diversity and changes of the cyanobacterial assemblage were investigated during a rice growth season and after harvest in a paddy field located in Fujian Province, China. The cyanobacterial populations were analyzed by a semi-nested PCR, followed by denaturing gradient gel electrophoresis analysis. Twenty-four phylotypes were identified from the denaturing gradient gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 35 publications
4
71
0
1
Order By: Relevance
“…In the present study, no phylotypes most similar to cyanobacteria were observed from the cDNA-DGGE analysis although cyanobacteria are known diazotrophs in the rice paddy (Khan et al 1994;Song et al 2005). In order to examine if a bias was generated by the nested PCR approach and/or from the DGGE analysis, two clone libraries from cDNA samples (UFB04:00 and FB04:00) were generated by direct amplification with the PolF/PolR primers.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, no phylotypes most similar to cyanobacteria were observed from the cDNA-DGGE analysis although cyanobacteria are known diazotrophs in the rice paddy (Khan et al 1994;Song et al 2005). In order to examine if a bias was generated by the nested PCR approach and/or from the DGGE analysis, two clone libraries from cDNA samples (UFB04:00 and FB04:00) were generated by direct amplification with the PolF/PolR primers.…”
Section: Discussionmentioning
confidence: 76%
“…The favorable balance of soil N of wetlands, wherein rice can be grown on the same land without any fertilizers and without any detectable decline in yield, attests to the signifi cance of cyanobacterial nitrogen fi xation. Also, indirect evidence for its potentiality is available through demonstrations of enhanced crop growth and yields [25][26][27][28]. The present investigation was aimed towards a less investigated domain of cyanobacteria -the rhizosphere, as a means of identifying isolates which can establish and proliferate in soil and prove better competitors when applied as biofertilizer consortia.…”
Section: Resultsmentioning
confidence: 99%
“…The members of this genus are capable of a variety of modes of C and N nutrition, which adapts them to diverse ecological habitats and the biotrophic transfer of fi xed N to the hosts [10]. Song et al [28] used semi nested PCR and DGGE to evaluate the cyanobacterial diversity and seasonal changes in a selected rice fi eld, and identifi ed 24 phylotypes, including Nostoc and Phormidium, some of which were specifi c to the stage of sampling (i.e. rice growth season).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria strains are able to fi x atmospheric nitrogen and enrich the soil, rice, wheat, willow, and other plants with this nutrient [8,[25][26][27]. This natural biofertilizer can play an important role in maintenance and buildup of soil fertility, consequently increasing development and yield of plants as discovered in oats, radish, rice, sugarcane, barley, tomato, chili, cotton, wheat, maize, lettuce, gillyfl ower, grapevine, and willow grown in favorable conditions [8,[25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%